2014
DOI: 10.1051/0004-6361/201322482
|View full text |Cite
|
Sign up to set email alerts
|

Supersonic turbulence in 3D isothermal flow collision

Abstract: Large scale supersonic bulk flows are present in a wide range of astrophysical objects, from O-star winds to molecular clouds, galactic sheets, accretion, or γ-ray bursts. Associated flow collisions shape observable properties and internal physics alike. Our goal is to shed light on the interplay between large scale aspects of such collision zones and the characteristics of the compressible turbulence they harbor. Our model setup is as simple as can be: 3D hydrodynamical simulations of two head-on colliding, i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 150 publications
0
14
0
Order By: Relevance
“…It is thus not clear whether we under-or over-estimate this particular effect. Secondly, radiative multi-dimensional shocks can generate and drive turbulence (Walder & Folini 1998) and turbulent thin-shells (Folini & Walder 2006;Folini et al 2014).…”
Section: Coolingmentioning
confidence: 99%
“…It is thus not clear whether we under-or over-estimate this particular effect. Secondly, radiative multi-dimensional shocks can generate and drive turbulence (Walder & Folini 1998) and turbulent thin-shells (Folini & Walder 2006;Folini et al 2014).…”
Section: Coolingmentioning
confidence: 99%
“…This thin shell is stable against linear instabilities but not necessarily against the nonlinear thinshell instability (NTSI; Vishniac 1994). The NTSI has been studied with hydrodynamic (Folini et al 2014) and magnetohydrodynamic (Heitsch et al 2007;McLeod & Whitworth 2013) simulations. However, unlike Rayleigh-Taylor or linear thin-shell instabilities (Grun et al 1991;Edens et al 2005;Ditmire & Edens 2008), the NTSI in a fluid or plasma has not yet been detected experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon has been identified in numerical simulations (e.g. Hunter et al 1986;Walder & Folini 2000;Audit & Hennebelle 2005;Heitsch et al 2005;Vázquez-Semadeni et al 2006Heitsch, Naab & Walch 2011;Inoue & Fukui 2013;Folini et al 2014, and others), being promptly related to the collapse of dense strucutures in the ISM and star formation, and analytically described by Vishniac (1994) as the nonlinear evolution of perturbations in shock-bounded slabs.…”
Section: Inverse Cascade: From Small To Large Scalesmentioning
confidence: 77%
“…As pointed before, radiative shocks in converging flows (see Heitsch et al 2005;Audit & Hennebelle 2005;Heitsch et al 2006;Bonnell et al 2006Bonnell et al , 2013 have been shown to be very efficient in forming dense and cold structures in the ISM, but not very efficient in driving supersonic turbulence though. Theoretical studies of these systems reveal that the main process that lead to the structuring of clumps is the NTLI, which is also known to result in small scale subsonic/transonic turbulent flows (Vishniac 1994;Folini et al 2014). …”
Section: Discussionmentioning
confidence: 99%